The Effect of Training, Motivation and Working Environment to Employee Performance in Bank XYZ - Mulyono Mulyono; Kasdono Kasdono; Adi Teguh Suprapto (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2018)
The purpose of this study to examine the effect of training, motivation and working environment on employee performance. Data collection techniques used by conducting interviews and distributing questionnaires to employees of Bank XYZ. The method of analysis used in this study is the multiple linear regression test. The unit of analysis in this study is individual and focuses on individual performance. The results showed there is a significant influence in T-test between Training, Motivation and Working Environment on Employee Performance, and there is a significant influence in F-test between the variables Training, Motivation and Work Environment on Employee Performance